2021
DOI: 10.1038/s41390-020-01353-x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone effectively attenuates acute and long-term consequences of neonatal repetitive procedural pain in a rat model

Abstract: BACKGROUND: Painful procedures in early life cause acute pain and can alter pain processing at a spinal level lasting into adulthood. Current methods of analgesia seem unable to prevent both acute and long-term hypersensitivity associated with neonatal pain. The current study aims to prevent acute and long-term hypersensitivity associated with neonatal procedural pain using methadone analgesia in rat pups. METHODS: Sprague-Dawley rat pups received either methadone (1 mg/kg) or saline prior to repetitive needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This is important as descending serotonergic RVM-spinal dorsal horn have been reported to act in a facilitatory way in neonates ( 26 ). In addition, the anti-nociceptive effect of 5-HT1aR becomes more apparent from postnatal day 4 onwards, and this coincides with progressive increase in acute hypersensitivity with cumulative exposure to repetitive needle pricking ( 14 16 , 23 ). 5-HT1aR in neonates inhibit nociceptive signaling through a reduced glutamate release from primary afferent terminals or by increasing the incidence of long-term depression induced inhibition of postsynaptic dorsal horn responses ( 28 , 29 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is important as descending serotonergic RVM-spinal dorsal horn have been reported to act in a facilitatory way in neonates ( 26 ). In addition, the anti-nociceptive effect of 5-HT1aR becomes more apparent from postnatal day 4 onwards, and this coincides with progressive increase in acute hypersensitivity with cumulative exposure to repetitive needle pricking ( 14 16 , 23 ). 5-HT1aR in neonates inhibit nociceptive signaling through a reduced glutamate release from primary afferent terminals or by increasing the incidence of long-term depression induced inhibition of postsynaptic dorsal horn responses ( 28 , 29 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 97%
“…Future studies should include local intrathecal administration to further specify the involvement of spinal 5-HT1aR and 5-HT3R in the observed effects. Lastly, baseline differences between animals exposed to repetitive needle pricking or tactile stimulation and undisturbed animals at 8 weeks of age, prior to re-incision were observed Nevertheless and based on within-group analysis any possible effects related to the differences in baseline value differences on post-operative mechanical sensitivity can be excluded ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies added a reinjury at 8 weeks to observe changes in pain threshold during adulthood because neonatal repeated procedural pain leads not only to acute shortterm hyperalgesia but also to changes in pain threshold in adulthood [9,48]. In this study, a reinjury was also established following previously described methods [9,48]. In brief, at week 8 (W8), for each relevant mouse, a hind paw was pricked with a needle.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Van den Hoogen et al 13 very recently reported in this journal that neonatal methadone analgesia is able to attenuate acute as well as long-term hypersensitivity associated with neonatal procedural pain in a rat model. In their paper the authors advocate for clinical studies to assess acute and long-term analgesic effectivity of methadone in neonates.…”
mentioning
confidence: 99%
“…In summary, the research of van den Hoogen et al, 13 which was recently published in this journal, provides exciting and stimulating information about the possible use of methadone for the treatment of neonatal pain in the neonatal intensive care unit. It also presents a very compelling case of using mechanism based analgesia during neonatal pain.…”
mentioning
confidence: 99%